STUDI ANALITIS TENTANG PEMAHAMAN GURU TERHADAP IMPLEMENTASI HOTS DALAM PERENCANAAN PEMBELAJARAN PRASEKOLAH - Ismiatun, Asih Nur; Andrisyah; Siregar, Masyunita; Harianja, Sri Indriani (Universitas Islam Negeri Ar-Raniry Banda Aceh, 2026)
The implementation of HOTS (Higher Order Thinking Skill) is the foundation for developing critical thinking skills in early childhood. This study aims to analyze the implementation of HOTS in the preparation of ECE learning plans. This study uses a quantitative descriptive method involving 31 ECE teacher respondents in West Java who were selected using a random sampling technique. The data collection technique used a questionnaire containing three indicators of the level of ECE teachers' understanding of HOTS implementation. The data analysis technique measures the centralization of data by measuring the mean. The results of the study indicate that most teachers have heard of HOTS but have not been able to fully explain the HOTS concept, teachers have not been able to differentiate precisely between the HOTS concept and cognitive development, awareness of HOTS implementation in ECE learning devices is already possessed by teachers and some have implemented it as seen from the OAVs (Operational Action Verbs) and the output of learning activities mentioned. ECE teachers' understanding of HOTS implementation must continue to be improved so that they can produce learning plans in accordance with the demands of 21st-century learning.